Malignancy in scars, chronic ulcers, and sinuses. Issue 6 (November 1963) - Cruickshank, A. H.; McConnell, E. Mavis; Miller, D. G.
Abstract : A collection of 44 cases of malignancy in scars, chronic ulcers, and sinuses, included the following predisposing lesions: a 20-year-old sinus from ischial bursitis, a 23-year-old bed sore, a congenital gumma about 50 years old, three burn scars (average age of scar 56 years), 11 sinuses from chronic osteomyelitis, and 27 chronic ulcers of the leg. The osteomyelitis cases included two rapidly fatal sarcomas, one in a sinus present for 16 years, the other in a 20-year-old sinus. The remaining tumours in this group were squamous carcinomas that developed in sinuses with an average duration of 37 years. In the cases of varicose ulcer, the ulcer had been present on the average for 21 years before the onset of malignancy. One patient in this group, with an ulcer not known to be more than five years old, developed a sarcoma that was fatal in six months. The biopsy diagnosis was difficult in 17 cases, including one of the cases of sarcoma. The difficulty was greatest in cases of osteomyelitis. The conditions discussed are now known as `Marjolin's ulcer'. In the present series, the degree of malignancy in tumours arising in scars may be low but the malignancy of tumours arising in chronic ulcers and sinuses may be high.